Linking seasonal N2O emissions and nitrification failures to microbial dynamics in a SBR wastewater treatment plant. (1st May 2021) - Gruber, Wenzel; Niederdorfer, Robert; Ringwald, Jörg; Morgenroth, Eberhard; Bürgmann, Helmut; Joss, Adriano
Highlights: Strong correlation of nitrite peaks, seasonal N2 O emissions and microbial dynamics. Reactors with a stable microbial community do not exhibit nitrification failure. AOB are quite stable, NOB disappear in disturbed reactors. Standard engineering approaches do not improve plant performance. Loss and gain of NOB activity coincides with loss and gain of filamentous bacteria. Abstract: Nitrous oxide (N2 O) is a strong greenhouse gas and causal for stratospheric ozone depletion. During biological nitrogen removal in wastewater treatment plants (WWTP), high N2 O fluxes to the atmosphere can occur, typically exhibiting a seasonal emission pattern. Attempts to explain the peak emission phases in winter and spring using physico-chemical process data from WWTP were so far unsuccessful and new approaches are required. The complex and diverse microbial community of activated sludge used in biological treatment systems also exhibit substantial seasonal patterns. However, a potentially causal link between the seasonal patterns of microbial diversity and N2 O emissions has not yet been investigated. Here we show that in a full-scale WWTP nitrification failure and N2 O peak emissions, bad settleability of the activated sludge and a turbid effluent strongly correlate with a significant reduction in the microbial community diversity and shifts in community composition. During episodes of impaired performance, we observed a significant reduction in abundance for filamentous and nitrite oxidizing bacteria in all affected reactors. In some reactors that did not exhibit nitrification and settling failures, we observed a stable microbial community and no drastic loss of species. Standard engineering approaches to stabilize nitrification, such as increasing the aerobic sludge age and oxygen availability failed to improve the plant performance on this particular WWTP and replacing the activated sludge was the only measure applied by the operators to recover treatment performance in affected reactors. Our results demonstrate that disturbances of the sludge microbiome affect key structural and functional microbial groups, which lead to seasonal N2 O emission patterns. To reduce N2 O emissions from WWTP, it is therefore crucial to understand the drivers that lead to the microbial population dynamics in the activated sludge. Graphical abstract: Image, graphical abstract